Bis[4-(dimethyl-amino)pyridinium] tetra-bromidodiphenyl-plumbate(IV). - Lo, Kong Mun; Ng, Seik Weng (International Union of Crystallography, 2008)
The Pb(IV) atom of the anion of the title salt, (C(7)H(11)N(2))(2)[PbBr(4)(C(6)H(5))(2)], is situated on a crystallographic center of inversion and exhibits a tetra-gonally compressed octa-hedral coordination. One of the two independent Br atoms acts as a hydrogen-bond acceptor towards the NH group of the cation.